KESIAPAN MADRASAH IBTIDAIYAH MUHAMMADIYAH SEBAGAI SEKOLAH SIAGA BENCANA DI KECAMATAN GONDANGREJO KARANGANYAR - Susilowati, Siti Azizah; Khoirunisa, Nanda (Universitas Muhammadiyah Surakarta, 2015)
The research aims was to determine the readiness of school-related disaster preparedness schoolin some Muhammadiyah Islamic elementary schools in District Gondangrejo. The object ofresearch is 5 Muhammadiyah Islamic elementary schools in the district spread Gondangrejo,Karanganyar. Collecting research data form the primary data using research instrument inthe form of questionnaires with quantitative descriptive analysis. The results showed that:1) the Muhammadiyah Islamic elementary schools located in District Gondangrejo acquirepreparedness index values between 0-32 with an average index value of 16 and included inkatagoti â€œNot Readyâ€, 2) overall parameters included in the category of â€œLowâ€ with the indexvalue between 3-30 with the highest parameter values in school policies and lowest parameteris the parameter emergency response plan. It was concluded that the MuhammadiyahIslamic Elementary School in District Gondangrejo Karanganyar not alert to the disaster.